Research on Interactive Teaching System and Method Based on Augmented Reality - Wang, Ziqi; Yang, Jian (Transactions on Economics, Business and Management Research, 2024)
This study provides an interactive teaching system and method based on augmented reality, belonging to the field of educational technology. The interactive teaching system and method based on augmented reality feature an interactive teaching system that includes a core processing module, a content creation and management module, a user interaction module, a data analysis and evaluation module, and a technical support and maintenance module. The learning behavior analysis unit tracks learning paths and interactive data, the effectiveness evaluation unit uses big data analysis to evaluate learning outcomes and the effectiveness of teaching strategies, the personalized recommendation unit recommends resources or adjusts paths based on student performance, utilizes deep learning prediction models for multidimensional learning effectiveness evaluation, provides real-time feedback, guides adjustments to teaching strategies, offers remote diagnostics, automatic updates, and fault prevention, adopts predictive maintenance strategies to reduce downtime, operates a 24/7 customer service system to instantly resolve technical issues, ensuring teaching activities are not disrupted.